Corrigendum. (September 2018) - Unknown
'Integrated Cellular Framework for Modeling Ecosystems: Theory and Applications', by Baha Uddin Kazi and Gabriel Wainer, published Online First on 11 March 2017 in the journal of Simulation with the DOI:10.1177/0037549717706007 . In this paper, the funding statement was incorrect and the acknowledgements section was not added in the Online First version. This has since been corrected in the Online First version of the article.